CONCEPT MAP: TERMINOLOGY OF CREED/THEOLOGY AND THE SCOPE OF STUDY OF MORAL THEOLOGY - Sembiring, Nurhaizan; Adawiyah, Rabiatul; Nurdiani, Nurdiani; Marisa, Siti (Proceeding International Seminar of Islamic Studies, 2024)
The creed is the basis, the foundation for building a building. The higher the building to be erected, the stronger the foundation must be. If the foundation is weak the building will quickly collapse. There is no building without a foundation. Akidah is the most fundamental problem in Islamic teachings, because it is the basis of the conception of the whole Islamic teachings. So that whether the deeds of humans or Muslims are accepted or not, in the sight of Allah it really depends on the creed itself. Akidah is a religious teaching about belief or belief in God. All divine religions teach about faith as the basis and principle of monotheism, so that from an early age the material of faith is taught to students. The creed that is deeply ingrained for its adherents cannot be bought or exchanged for any object. Humans cannot escape from belief and belief. Without trust and belief, it is impossible for humans to live. People will not dare to eat and drink until they are sure and believe that these foods and drinks do not harm themselves. Likewise all other human activities related to life and life. Everything is inseparable from the elements of belief and belief.